2020
DOI: 10.1051/e3sconf/202020206005
|View full text |Cite
|
Sign up to set email alerts
|

Do we care enough? revisiting land subsidence and coastal spatial planning policy in Semarang, Indonesia

Abstract: Land subsidence is a common unsustainable pattern of land use on young sediment coasts worldwide, such as Semarang coastal area. The impact had already transformed its northeast area become permanently tidal flooded, damage in houses and streets, and economic loss. However, local government efforts are noticeably as band-aid measures, which can lead to further mismanagement in halting land subsidence. Given that, this research aimed to evaluate how the latest coastal spatial planning policy in Semarang respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Our prior study Hamdani et al, [42] found that land subsidence is currently not incorporated in spatial planning. In this continued study, we found that in City Official's One Map website, we could easily find the land subsidence map.…”
Section: Revisiting Spatial Planning Policymentioning
confidence: 99%
“…Our prior study Hamdani et al, [42] found that land subsidence is currently not incorporated in spatial planning. In this continued study, we found that in City Official's One Map website, we could easily find the land subsidence map.…”
Section: Revisiting Spatial Planning Policymentioning
confidence: 99%
“…This technique was commonly used to evaluate development policy. Content analysis was formerly used as a tool to understand how a theoretical concept was being interpreted into policy (Handayani et al, 2019), the comprehensiveness of policy in addressing environmental hazards (Hamdani et al, 2020), the capability of strategic planning in resolving land degradation (Oliveira et al, 2018), and developing inclusive recommendation in updating smart city strategies (Bednarska-Olejniczak et al, 2019).…”
Section: Data Analysis and Collection Techniquesmentioning
confidence: 99%
“…Strategies and adaptive mitigation measures need to be developed to reduce the risk of disasters in coastal areas, particularly floods [5]. This problem becomes "homework" for all stakeholders, particularly the government, considering that coastal areas undergo continuous dynamics in natural conditions, socio-economic factors, and oceanographic processes [11,12]. Disaster risk is proportional to the hazards present in a location but varies based on vulnerability and capacity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing cloud computing is an efficient way to conduct flood risk assessment, as concluded by the study. Some researcher have explained that this technology involves utilizing virtual cloud or computer resources for computational purposes [11,12]. This method could be implemented by Google Earth Engine (GEE) to assess flood risks by relying on Synthetic Aperture Radar (SAR) data for inundation extraction and Landsat-8 for evaluating the distribution of affected land use [18].…”
Section: Introductionmentioning
confidence: 99%